Rapid magnetic resonance-guided near-infrared mapping to image pulsatile hemoglobin in the breast - Li, Zhiqiu (2010)
A near-IR (NIR) tomography system with spectral-encoded sources was built to quantify the temporal contrast in human breast tissue using guidance from magnetic resonance imaging. The systems were integrated with a custom breast coil interface to provide simultaneous acquisition. The NIR signal was synchronized to simultaneous finger pulse oximeter plethysmogram, which offered a frequency reference. A 0:1 s temporal delay of the absorption pulse within adipose tissue relative to fibroglandular tissue was found, in an initial human study, showing the potential for novel contrast imaging of fast flow signals in deep tissue.